Inclusive Education in a Montessori Environment : A Case Study - Bodero Arcos, Joselyne (My University, 2025)
This thesis aimed to analyze inclusive education in a Montessori learning environment. Therefore, a case study of a classroom in a Montessori school was taken place to explore teachers’ perspectives and approaches towards inclusive education, observe inclusive education practices, and identify inclusive education dimensions that could be present in this environment. It is qualitative research that uses both semi-structured interviews and observations in a form of a field diary to get a deep understanding of how inclusive education takes place in a learning environment that implements Montessori pedagogy. The results show five inclusive dimensions of this learning environment. Accessibility, Participation, and Learning and Teaching Process were found by interviews and observations. Values and Conditions involved information that could be only collected by interviews. However, further observations could be done using the analysis of this study to provide more and even deeper analysis of these topics. Regarding accessibility, the results revealed that there was accessibility related to physical environment and communication and, indeed, this accessibility concerned diversity in learning, social/cultural and developmental aspects. In relation to participation, the results found the principles proposed by Black-Hawkins (2010), that is, participation involves everyone, implies the active right to join in, is concerned with responses to diversity, is based on respectful relationships, is a never-ending process and it is distanced conceptually from the notions of Special Educational Needs (SEN). With regard to learning and teaching process, the results show that teachers prepare their environment and provide individualized attention to better address the diversity in class. Also, values such as sense of belonging, welcoming of diversity, teachers’ flexibility, and conflict resolution were found. Finally, four conditions for inclusion were visible: reflection, use of evidence, collaboration and willingness to seek training and support. Thus, the findings of this study suggest that this Montessori learning environment presents many strategies and elements of inclusion and, therefore, it can be considered as inclusive. Since inclusion is a broad and a very deep concept, further research can be done to provide more information, analysis and a deeper understanding of this topic. Also, more perspectives can be collected such as those of teachers of other classrooms, management team or the principal of the school.
Keywords: inclusive education, inclusion, Montessori, diversity, accessibility, participation, learning, values, conditions